Testing the CRISPR-Cas9 and glmS ribozyme systems in Leishmania tarentolae - Turra, Gino L.; Schneider, Luzia; Liedgens, Linda; Deponte, Marcel (Molecular and biochemical parasitology, 2021)
Leishmania parasites include important pathogens and model organisms and are even used for the production of recombinant proteins. However, functional genomics and the characterization of essential genes are often limited in Leishmania because of low-throughput technologies for gene disruption or tagging and the absence of components for RNA interference. Here, we tested the T7 RNA polymerase-dependent CRISPR-Cas9 system by Beneke et al. and the glmS ribozyme-based knock-down system in the model parasite Leishmania tarentolae. We successfully deleted two reference genes encoding the flagellar motility factor Pf16 and the salvage-pathway enzyme adenine phosphoribosyltransferase, resulting in immotile and drug-resistant parasites, respectively. In contrast, we were unable to disrupt the gene encoding the mitochondrial flavoprotein Erv. Cultivation of L. tarentolae in standard BHI medium resulted in a constitutive down-regulation of an episomal mCherry-glmS reporter by 40 to 60%. For inducible knock-downs, we evaluated the growth of L. tarentolae in alternative media and identified supplemented MEM, IMDM and McCoy’s 5A medium as candidates. Cultivation in supplemented MEM allowed an inducible, glucosamine concentration-dependent down-regulation of the episomal mCherry-glmS reporter by more than 70%. However, chromosomal glmS-tagging of the genes encoding Pf16, adenine phosphoribosyltransferase or Erv did not reveal a knock-down phenotype. Our data demonstrate the suitability of the CRISPR-Cas9 system for the disruption and tagging of genes in L. tarentolae as well as the limitations of the glmS system, which was restricted to moderate efficiencies for episomal knock-downs and caused no detectable phenotype for chromosomal knock-downs.
Available online 6 November 2020
Gesehen am 10.09.2021